Unraveling TEOSINTE BRANCHED1/CYCLOIDEA/PROLIFERATING CELL FACTOR Transcription Factors in Safflower: A Blueprint for Stress Resilience and Metabolic Regulation - Lili Yu; Xintong Ma; Mingran Dai; Yue Chang; Nan Wang; Jian Zhang; Min Zhang; Na Yao; Abdul Wakeel Umar; Xiuming Liu (Molecules)
Safflower (Carthamus tinctorius L.), a versatile medicinal and economic crop, harbors untapped genetic resources essential for stress resilience and metabolic regulation. The TEOSINTE BRANCHED1/CYCLOIDEA/PROLIFERATING CELL FACTOR (TCP) transcription factors, exclusive to plants, are pivotal in orchestrating growth, development, and stress responses, yet their roles in safflower remain unexplored. Here, we report the comprehensive identification and characterization of 26 safflower TCP genes (CtTCPs), categorized into Class I (PROLIFERATING CELL FACTOR, PCF) and Class II (CINCINNATA and TEOSINTE BRANCHED1/CYCLOIDEA, CIN and CYC/TB1) subfamilies. Comparative phylogenetics, conserved motif, and gene structure analyses revealed a high degree of evolutionary conservation and functional divergence within the gene family. Promoter analyses uncovered light-, hormone-, and stress-responsive cis-elements, underscoring their regulatory potential. Functional insights from qRT-PCR analyses demonstrated dynamic CtTCP expression under abiotic stresses, including abscisic acid (ABA), Methyl Jasmonate (MeJA), Cold, and ultraviolet radiation b (UV-B) treatments. Notably, ABA stress triggered a significant increase in flavonoid accumulation, correlated with the upregulation of key flavonoid biosynthesis genes and select CtTCPs. These findings illuminate the complex regulatory networks underlying safflower’s abiotic stress responses and secondary metabolism, offering a molecular framework to enhance crop resilience and metabolic engineering for sustainable agriculture